The Use of DeepL as a Translation Tool in English Language Learning: Insights from Indonesian EFL University Students - A’yun, Silvianida Qurrota; Karim, Sayit Abdul; Matas, Gordan; Radjaban, R.Yohanes; Winarna, Winarna (Institut Agama Islam Negeri Kudus, 2025)
The rapid advancement of digital technologies has transformed language learning practices, for instance, the use of DeepL translation tools for machine translation. It plays a growing role in facilitating comprehension, vocabulary development, and academic literacy among EFL learners. This study provides empirical evidence of how DeepL shapes students’ learning efficiency and translation strategies. This mixed-methods study explores the perceptions and challenges of 27 fourth-year English Language Education Study Program (ELESP) students at Universitas Teknologi Yogyakarta regarding DeepL as a translation tool in their language learning. Employing questionnaires and semi-structured interviews for data collection, the research gathered both quantitative and qualitative data. The questionnaire explored students' overall perceptions, while interviews delved into the specific challenges encountered by six selected students, using a purposive sampling technique across varying proficiency levels: two students with high proficiency, two students with medium proficiency, and two students with low proficiency, as indicated by the analyzed questionnaire scores. Furthermore, the researchers analyzed the questionnaire results through data checking, coding categories, and compared them across the highest, middle, and lowest categories, analyzing the results descriptively. Meanwhile, for the semi-structured interview, the results were analyzed using an interactive model, comprising data collection, data reduction, data display, and drawing conclusions. Findings indicate positive student perceptions. Quantitative analysis of questionnaire data revealed overwhelmingly positive perceptions, with 81.5% and 66.7% of students showing high agreement on key positive statements about DeepL's utility. However, the qualitative data reveal that all interviewed students face challenges, particularly the time-consuming process of double-checking translations due to the uncertainty of meaning. This study highlights DeepL's significant role in facilitating language learning while also underscoring the need for students to develop critical evaluation skills.